Using Mobile-Assisted Language Learning (MALL) to Improve Junior High School Students’ Reading Comprehension of Descriptive Texts - Indah Salza Legiasih; Maisa Maisa; Linda Linda (ANTHOR: Education and Learning Journal, 2026)
This study aims to investigate the effectiveness of Mobile-Assisted Language Learning (MALL) in improving junior high school students’ reading comprehension of descriptive texts. A quantitative approach was employed using a pre-experimental design with a one-group pre-test and post-test model. The participants were 29 seventh-grade students from a junior high school in Indonesia. Data were collected through reading comprehension tests administered before and after the implementation of MALL-based learning activities. The instrument consisted of multiple-choice questions measuring four aspects of reading comprehension: identifying the main idea, locating specific information, recognizing generic structure, and understanding vocabulary meaning. The data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test with SPSS because the data were not normally distributed. The results showed that the students’ mean score increased from 67.67 in the pre-test to 69.54 in the post-test. However, the Wilcoxon Signed-Rank Test indicated that the difference between the pre-test and post-test scores was not statistically significant (Sig. = 0.401 > 0.05). These findings indicate that although MALL provided opportunities for students to interact with descriptive texts through mobile-based learning activities, its implementation did not significantly improve students’ reading comprehension within the treatment period. Therefore, future studies are recommended to employ longer treatment periods and incorporate more varied mobile-based learning activities to maximize the potential of MALL for developing students’ reading comprehension.